Higher Education in Hungary in the Time of the Pandemic - Anetta Bacsa-Bán (AS: Andragoška Spoznanja)
In the spring of 2020, the coronavirus pandemic presented the world with new challenges. In the first half of March, parallel to the spread of COVID-19, teaching and lecture halls, colleges and other facilities in universities and university campuses were emptied almost simultaneously. Almost overnight, all higher educational institutions switched from face-to-face teaching to online teaching, namely absentee or distance learning. In our study, we surveyed students (both Hungarian and English-speaking students) and higher education faculty at the end of the second semester of the 2019/2020 academic year to explore their experiences with online education during the pandemic. In our analysis, we explore some aspects of distance learning during the pandemic that we consider important, and we seek to compare the student and teacher views. The results show that the introduction of fully online teaching during the pandemic was relatively smooth, but this period was not without challenges and difficulties that manifested themselves in the learning and teaching process, in the availability of learning materials, in the digital skills of students, and in the work overload of teachers. In summary, however, the response of higher education to digitalisation today, besides its inevitability, is to prioritise the incorporation of past experiences in determining the focus of further development.